2006
DOI: 10.1073/pnas.0510237103
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 1A receptors in the living brain of Alzheimer's disease patients

Abstract: [F-18]MPPF ͉ brain 5-HT1A receptors ͉ neuronal loss ͉ positron emission tomography E xtensive brain cell loss in vulnerable cortical neuronal populations is one of the most striking hallmarks of Alzheimer's disease (AD). Neuronal loss appears to be correlated with the presence of abundant intraneuronal neurofibrillary tangles (NFTs) and is also an excellent parameter to correlate with the degree of dementia (1). Among the vulnerable neurons affected in the earliest stages of the disease are large pyramidal neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
155
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(166 citation statements)
references
References 49 publications
(35 reference statements)
10
155
1
Order By: Relevance
“…As expected, we found that 5-HT content was selectively reduced in the PFC of Ab-treated animals, but not in the STR or NAc. These results are supported by demonstrations that impairments of the 5-hydroxytryptaminergic system are present in the very early stages of AD (Versijpt et al, 2003;Egashira et al, 2005;Kepe et al, 2006). In this regard, it is well known that impaired 5-hydroxytryptaminergic neurotransmission in the prefrontal area is central to depressive disorders (Krishnan and Nestler, 2008), but could also have an important role in the pathogenesis of several neurodegenerative diseases Egashira et al, 2005).…”
Section: Discussionmentioning
confidence: 65%
“…As expected, we found that 5-HT content was selectively reduced in the PFC of Ab-treated animals, but not in the STR or NAc. These results are supported by demonstrations that impairments of the 5-hydroxytryptaminergic system are present in the very early stages of AD (Versijpt et al, 2003;Egashira et al, 2005;Kepe et al, 2006). In this regard, it is well known that impaired 5-hydroxytryptaminergic neurotransmission in the prefrontal area is central to depressive disorders (Krishnan and Nestler, 2008), but could also have an important role in the pathogenesis of several neurodegenerative diseases Egashira et al, 2005).…”
Section: Discussionmentioning
confidence: 65%
“…Vaishnavi et al (1) and Vlassenko et al (2) show that higher levels of aerobic glycolysis are concentrated in the default mode network (DMN), an anatomically defined brain network-involving the medial temporal lobe and the medial prefrontal subsystems that converge for integration in the posterior cingulate gyruspreferentially active when individuals Brain regional correlations between markers for amyloid tau deposition, glucose hypometabolism, and neuronal losses and corresponding alterations in neuropsychiatric measures were demonstrated in humans with AD and mild cognitive impairment (MCI) (10). These results strengthened earlier suggestions that clinical symptoms characteristic for AD stem from the disruption of major neuronal circuits caused by the extensive loss of neurons forming these circuits associated with early pathological Aβ and τ deposition initially affecting the entorhinal cortex.…”
mentioning
confidence: 99%
“…25 Regional cortical hypometabolism correlates with greater cognitive losses, and [ 18 F]FDG-PET can also differentiate patients with MCI from those with AD and controls (figure 3). 71,72 Diagnostic accuracy for AD seems better when [ 18 F]FDG-PET is added to the standard clinical assessment of dementia, providing increased sensitivity and specificity of diagnosis that is similar to that observed on clinical assessment 4 years after baseline. 73 In September 2004, the US Centers for Medicare and Medicaid Services approved Medicare reimbursement for [ 18 F]FDG-PET scans to assist with the differential diagnosis of AD and frontotemporal dementia, which is useful clinical information since the latter dementia does not seem to respond well to currently available symptomatic treatments.…”
Section: Petmentioning
confidence: 93%
“…91 Our group has developed a fluorine-18 tau and amyloid PET probe, [ 18 figure 3). 72 The differential binding potential of MPPF in the hippocampus is indicative of neuronal losses and might eventually provide an early diagnostic measure even before symptoms are present.…”
Section: F]-bay94-9172-pet or Trans-4-(n-methyl-amino)-4l'-{2-[2-(2-[mentioning
confidence: 99%